Update on MRI in pediatric intracranial germ cell tumors—The clinical and radiological features - Yang, Mingwen; Wang, Jian; Zhang, Lin; Liu, Jungang (Frontiers in Pediatrics, 2023)
Intracranial germ cell tumors (iGCTs) are uncommon brain tumors that mainly occur in children. Differ in histology, location and gender, iGCTs were often divided into germinomas and non-germinomatous germ cell tumors (NGGCTs). Early diagnosis and timely treatment are crucial to iGCTs which are with substantial variation in the prognosis among different subtypes. This review summarized the clinical and radiological features of iGCTs at different sites, and reviewed the recent advances in neuroimaging of iGCTs, which can help early predict tumor subtypes and guide the clinical decision-making.